Diagnostic accuracy for the epileptogenic zone detection in focal epilepsy could be higher in FDG-PET/MRI than in FDG-PET/CT - Kikuchi, Kazufumi (Eur Radiol, 2020)
OBJECTIVES: To examine the utility of FDG-PET/MRI in patients with epilepsy by comparing the diagnostic accuracy of PET/MRI and PET/CT in epileptogenic zone (EZ) detection. METHODS: This prospective study included 31 patients (17 males, 14 females) who underwent surgical resection for EZ. All patients were first scanned using FDG-PET/CT followed immediately with FDG-PET/MRI. Two series of PET plus standalone MR images were interpreted independently by five board-certified radiologists. A 4-point visual score was used to assess image quality. Sensitivities and visual scores from both PETs and standalone MRI were compared using the McNemar test with Bonferroni correction and Dunn’s multiple comparisons test. RESULTS: The EZs were confirmed histopathologically via resection as hippocampal sclerosis (n = 11, 35.5%), gliosis (n = 8, 25.8%), focal cortical dysplasia (n = 6, 19.4%), and brain tumours (n = 6, 19.4%) including cavernous haemangioma (n = 3), dysembryoplastic neuroepithelial tumour (n = 1), ganglioglioma (n = 1), and polymorphous low-grade neuroepithelial tumour of the young (n = 1). The sensitivity of FDG-PET/MRI was significantly higher than that of FDG-PET/CT and standalone MRI (FDG-PET/MRI vs. FDG-PET/CT vs. standalone MRI; 77.4–90.3% vs. 58.1–64.5% vs. 45.2–80.6%, p < 0.0001, respectively). The visual scores derived from FDG-PET/MRI were significantly higher than those of FDG-PET/CT, as well as standalone MRI (2.8 ± 1.2 vs. 2.0 ± 1.1 vs. 2.1 ± 1.2, p < 0.0001, respectively). Compared to FDG-PET/CT, FDG-PET/MRI increased the visual score (51.9%, increased visual scores of 2 and 3). CONCLUSIONS: The diagnostic accuracy for the EZ detection in focal epilepsy could be higher in FDG-PET/MRI than in FDG-PET/CT. KEY POINTS: • Sensitivity of FDG-PET/MRI was significantly higher than that of FDG-PET/CT and standalone MRI (FDG-PET/MRI vs. FDG-PET/CT vs. standalone MRI; 77.4–90.3% vs. 58.1–64.5% vs. 45.2–80.6%, p < 0.0001, respectively). • Visual scores derived from FDG-PET/MRI were significantly higher than those of FDG-PET/CT and standalone MRI (2.8 ± 1.2 vs. 2.0 ± 1.1 vs. 2.1 ± 1.2, p < 0.0001, respectively). • Compared to FDG-PET/CT, FDG-PET/MRI increased the visual score (51.9%, increased visual scores of 2 and 3). ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00330-020-07389-1) contains supplementary material, which is available to authorized users.